PEMBERDAYAAN KELOMPOK PKK DESA TEGALREJO DALAM PEMANFAATAN TEPUNG PISANG KEPOK MENJADI SOES KERING - Desti Ambar Wati; Dera Elva Junita; Dhifa Nadia Zahra; Aqila Nur Fadhillah; Nikmah Oktaviyeni; Dwi Rahma Sari (Ikatan Sarjana Gizi Indonesia, 2025)
Kepok banana (Musa paradisiaca Linn) is one of the leading horticultural commodities in Lampung Province with great potential as a raw material for food processing, particularly for banana chips and banana flour. Kepok bananas contain beneficial nutrients such as high dietary fiber, resistant starch, low glycemic index, and potassium, which can help regulate blood glucose and blood pressure. However, bananas are highly perishable fruits, thus requiring processing to extend shelf life and increase added value. This community service activity aimed to enhance the skills of PKK (Family Welfare Movement) members in Tegalrejo Village, Pringsewu Regency, in processing kepok bananas into flour and food products such as dry choux pastry. The methods used included observation, trial-and-error flour and pastry production, organoleptic testing, socialization, and demonstration. The results showed that the community participated enthusiastically throughout the process, and the best formulation for the dry choux pastry was a 25% substitution with kepok banana flour. This activity also successfully improved nutrition knowledge, entrepreneurship motivation, and awareness of local food potential. It is expected that this program will continue through intensive mentoring and the development of local food-based enterprises to support community food security and self-sufficiency